Laser-based technologies for sustainable manufacturing - Kumar, Avinash (Advances in manufacturing, design and computational intelligence techniques, 2023)
The text provides scientific and technological insights on novel techniques of design and manufacturing using laser technologies. It showcases applications of laser micromachining in the biomedical industry, laser-based manufacturing processes in aerospace engineering, and the high-precision laser cutting in-home appliance sector